Two new angiosperm leaf morphotypes from the Anfiteatro de Ticó Formation (mid-Aptian) Santa Cruz Province, Argentina - Romero, Edgardo Juan (2016)
Floodplain deposits of the Anfiteatro de Ticó Formation (Baqueró Group, Aptian), in Patagonia (Argentina), are rich in plant remains and contain some of the oldest angiosperm records of southern Gondwana. Many gymnosperm and pteridophyte species, as well as three morphotypes of medium sized angiosperm leaves, have already been described from this unit at different fossiliferous outcrops. We report two new angiosperm morphotypes from the Bajo Tigre locality. Both morphotypes (AT1 and AT2) consist of nano- to microphyllous leaves, nearly elliptic, with untoothed margins and pinnate brochidodromous venation. These leaves mostly exhibit characteristics of a high first or low second rank vein system. This combination of characters is associated with early angiosperm evolution. Morphotype AT1 is similar to one of the brochidodromous morphotypes from the La Cantera Formation (uppermost Aptian), which could be possibly conspecific. Morphotype AT2 has gross features already observed in leaf records from the younger Kachaike Formation (Albian ̶ lower Cenomanian) though they differ in lamina shape and secondary venation features. The angiosperm leaves of the Anfiteatro de Ticó Formation suggest that the early stages of angiosperm evolution in Patagonia had included forms with more than one type of growth habit.